Emerging markets and financial resilience decoupling growth from turbulence - Hooy, Chee Wooi; Ali, Ruhani; Rhee, S. Ghon (Palgrave Macmillan, 2013)
The biggest challenge for emerging markets is in finding ways to sustain its current trajectory and taking a more decisive role in shaping the global financial architecture to ensure sustainable growth. Specifically, the book covers topics in financial markets and development, international finance, foreign direct investment, portfolio management, corporate finance, and banking.